Effectiveness of a Clinically Relevant Educational Program for Improving Medical Communication and Clinical Skills of International Medical Graduates - Watt, David; Violato, Claudio; Lake, Deidre; Baig, Lubna (Canadian Medical Education Journal, 2010)
Background: To assess the efficacy of a 16 week, intensive, full-time medical communication and clinical skills educational program – Medical Communication Assessment Project (M-CAP) – at the Universities of Calgary and Alberta for improving medical communication, clinical skills and professionalism of international medical graduates (IMGs). There is an 8 week didactic course (language instructors, standardized clinical case scenarios) and an 8 week supervised clinical placement. Method: In Study 1, 39 IMGs (mean age = 35.6) participated in the M-CAP program and were assessed in English language proficiency in a pre- post-test design and on an in training evaluation report (ITER) by practicum physicians. In Study 2, there were 235 IMGs (mean age = 39.2). In addition to the pre- post-test design, there was a comparison group analysis on OSCE data employing multivariate analysis of variance (MANOVA). Pre- post-test data were also collected on ITERs during the practicum as was IMG reported program efficacy data. Results: The findings show that the participants in the M-CAP program have 1) very large gains in language proficiency (listening and speaking, reading and writing; p < .001), and 2) high ratings on scales from the practicum physicians. The between group analyses showed that M-CAP participants outperformed the non M-CAP participants on clinical skills and professionalism (p < .05). The IMGs gave very positive ratings to the M-CAP program. Conclusions: IMGs who participated in a clinically relevant educational program improved their English language proficiency, clinical skills and professionalism for medical practice in a host country.